Long-term health and socioeconomic consequences of child labor: Evidence from Brazil - Xuelian Zhang (Rutgers University, Department of Economics, 2012)
Child labor may impose positive and negative, direct and indirect effects on the long-term development of an individual. This study employs the Brazil Living Standards Measurement Study Survey to examine the long-run consequences of child labor on an adults income, health and educational attainment. When possible, the estimated models take into account of possible endogeneity and measurement error problems. The results suggest that early working has a negative and substantial income impact on rural residents and no impact on urban residents when controlling for schooling and health conditions. Child labor is associated with a worse self-assessed health index for rural adults and higher probability of getting health problems for both urban and rural adults. As for the schooling effect, the later one enters the labor market, the more years of schooling he obtains. While both the income and health impacts of child labor on rural residents are greater than those on urban residents, urban residents suffer greater adverse schooling impacts than their rural peers. My findings make a strong call to reduce child labor in Brazil and other developing countries. Moreover, the different effects of early working on urban and rural adults should be taken into account when child labor policies are proposed.
Keywords: J31; I10; I21; 330; Child labor; Long-term; Consequence; Brazil; Child labor; Long-term; Consequence; Brazil